How Strategic International Human Resource (IHR) Strategies can manage Organizational Performance Challenges - Gerald, Rossano V. (Archives of Business Research, 2018)
The global marketplace has become an economic reality in which the United States could be considered a dominant player, but some economists have stated that its position in this global economic environment has been declining in previous decades due to the European Union, Asian, and Emerging Markets. With that in mind, according to Wiley (1996) study, since the late 90s, most employers have been battling the benefits, conflicts, and challenges that come with a culturally diverse workplace. The advantage of a different environment is that it will bring about a broad range of knowledge, awareness, and viewpoints from people that were brought up in different cultural environments. As a result, a robust international position will require that human resource managers (HRM) are prepared to function effectively and efficiently in a goal-oriented environment. These managers must also appreciate cultural diversity and understand the complexities of the global climate and be willing to adapt their skills and strategies to cope with the international business challenges. This research paper will reveal how the GLOBE (Global Leadership and Organizational Behavior Effectiveness) techniques can be used to develop Human Resource Management Strategies to empower managers to do whatever is necessary to achieve organizational goals with the appropriate resources.